Soul raging [large type] - Kendig, Ronie (Kendig, Ronie. Book of the wars, 2021)
Sometimes, the only hope is the enemy. Leif Metcalfe is done waiting for answers and seizes control, a move that comes with a high price and a deadly risk: teaming up with the enemy. He can only hope that what he uncovers will heal the wounds he's inflicted on those he loves. Iskra Todorova believes Leif is on a collision course with death and knows firsthand the irrevocable cost of that path to the soul. While trying to protect her daughter and intervene with Leif, Iskra is forced to set her sights on the man behind the evil organization ArC--Ciro Veratti. Torn apart by injuries and opposing views on how to handle Leif's act of treachery, team Reaper hunts one of their own. The only thing they agree on is not stopping but starting the final battle prophesied in the Book of the Wars.